Stability and bone loss around submerged and non-submerged implants in diabetic and non-diabetic patients: a 7-year follow-up - Saeed AL ZAHRANI; Abdullah Abdulaziz AL MUTAIRI (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract To evaluate peri-implant bone loss (PIBL) and stability around submerged and non-submerged dental implants in patients with and without type 2 diabetes mellitus (T2DM). Thirty-five T2DM and non-diabetic (NT2DM) patients were included in this study. Demographic data were recorded using a questionnaire and PIBL was measured on digital radiographs. Resonance frequency analysis (RFA) was carried out for each implant at the time of fixture placement and at 3 months in both groups. P values less than 0.05 were considered statistically significant. One hundred and eighteen dental implants with a mean height of 10 to 12 mm and 3.3 to 4.1 mm in diameter were placed. The comparison of the mean RFA values at baseline and at 3 months was statistically significant (p = 0.008) in T2DM patients. The inter-group mean RFA values at baseline and at 3 months were not significant (p > 0.05). PIBL was significantly high in T2DM as compared to NT2DM patients at each follow-up (p < 0.05). At 2, 3, and 7 years, non-submerged dental implants showed significantly high PIBL in T2DM patients as compared to NT2DM individuals (p<0.05). The results of the present clinical study demonstrate increased PIBL around non-submerged single-tooth implant-supported restorations in T2DM patients, which may be due to the immune inflammatory status.